Design of Novel Compound Fresnel Lens for High-Performance Photovoltaic Concentrator - Lei Jing; Hua Liu; Huifu Zhao; Zhenwu Lu; Hongsheng Wu; He Wang; Jialin Xu (International Journal of Photoenergy)
We present a new design of compound Fresnel-R concentrator which is composed of two lenses: a primary lens (Fresnel lens) that works by total internal reflection at outer sawteeth but refraction at inner sawteeth, and a ringed secondary lens that works by refraction. In contrast to previous Fresnel lens concentrators, this design increases the acceptance angle, improves the irradiance uniformity on the solar cell, and reduces the aspect ratio significantly. Meanwhile several sawteeth of the primary Fresnel lens can correspond to a same ring of secondary lens, which will efficiently lower the complexity of designing and manufacturing. Moreover, in order to reduce the influence of manufacturing tolerances and to increase the optical efficiency further, the central part of the bottom of the secondary lens which directly adhered to the solar cell is designed as a cone-shaped prism to collect the sunlight that does not reach the solar cell. Finally, we provide simulations and analyses of the design method an optical efficiency more than 80% and an aspect ratio smaller than 0.5 can be achieved.